Guillain‐Barré syndrome and COVID‐19: A 1‐year observational multicenter study. (27th July 2022) - Filosto, Massimiliano; Cotti Piccinelli, Stefano; Gazzina, Stefano; Foresti, Camillo; Frigeni, Barbara; Servalli, Maria Cristina; Sessa, Maria; Cosentino, Giuseppe; Marchioni, Enrico; Ravaglia, Sabrina; Briani, Chiara; Castellani, Francesca; et al.
Abstract: Background and purpose: Many single cases and small series of Guillain–Barré syndrome (GBS) associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection were reported during the coronavirus disease 19 (COVID‐19) outbreak worldwide. However, the debate regarding the possible role of infection in causing GBS is still ongoing. This multicenter study aimed to evaluate epidemiological and clinical findings of GBS diagnosed during the COVID‐19 pandemic in northeastern Italy in order to further investigate the possible association between GBS and COVID‐19. Methods: Guillain–Barré syndrome cases diagnosed in 14 referral hospitals from northern Italy between March 2020 and March 2021 were collected and divided into COVID‐19‐positive and COVID‐19‐negative. As a control population, GBS patients diagnosed in the same hospitals from January 2019 to February 2020 were considered. Results: The estimated incidence of GBS in 2020 was 1.41 cases per 100, 000 persons/year (95% confidence interval 1.18–1.68) versus 0.89 cases per 100, 000 persons/year (95% confidence interval 0.71–1.11) in 2019. The cumulative incidence of GBS increased by 59% in the period March 2020–March 2021 and, most importantly, COVID‐19‐positive GBS patients represented about 50% of the total GBS cases with most of them occurring during the two first pandemic waves in spring and autumn 2020. COVID‐19‐negative GBS cases from March 2020 to March 2021 declined by 22% compared to February 2019–February 2020. Conclusions: Other than showing an increase of GBS in northern Italy in the "COVID‐19 era" compared to the previous year, this study emphasizes how GBS cases related to COVID‐19 represent a significant part of the total, thus suggesting a relation between COVID‐19 and GBS. Abstract : By showing an increase of Guillain–Barré syndrome (GBS) cases during the first two pandemic waves of coronavirus disease 19 (COVID‐19) in northern Italy and emphasizing that COVID‐19‐positive GBS patients represent about 50% of the total GBS cases, this study supports a relation between COVID‐19 and GBS. Physicians should keep in mind GBS as a possible complication of COVID‐19 infection to make an early diagnosis and start an appropriate treatment.